Developing a Core Outcome Set for Clinical Trials of Chinese Medicine for Hyperlipidemia - Geng Li; Geng Li; Ruxue Han; Mingjun Lin; Zehuai Wen; Zehuai Wen; Zehuai Wen; Zehuai Wen; Xiankun Chen; Xiankun Chen; Xiankun Chen; Xiankun Chen (Frontiers Media S.A., 2022)
Background: Chinese medicine (CM) is widely used for treating hyperlipidemias, especially in China. However, the heterogeneity of outcomes measured and reported across trials exacerbates the obstacles of evidence synthesis and effectiveness comparison. In this study, we develop a core outcome set (COS) for CM clinical trials for hyperlipidemia (COS-CM-Hyperlipidemia) to tackle the outcome issues.Methods: We generated candidate outcomes through a systematic review of interventional and observational studies of Chinese medicine for hyperlipidemias. The comprehensive search strategy was employed. Study selection and data collection were independently done by two researchers. We searched clinical trial registry platform to supplement the outcomes list extracted by systematic review. Then, we conducted a three-round Delphi survey. The stakeholders were hyperlipidemia patients, clinicians or researchers, in either CM/integrated Chinese or Western medicine, clinical pharmacy, clinical epidemiology or statisticians, or editors of important relevant journals and an ethicist. They used a 9-point Likert scale to determine how important they felt each outcome was in determining treatment success. A consensus meeting was held to confirm the final COS, based on the Delphi survey results.Results: We identified a total of 433 outcomes from 3,547 articles, and 28 outcomes from 367 registered trials. After standardization, we selected 71 outcomes to develop a preliminary outcome list for further consensus. After three Delphi survey rounds and one consensus meeting, the most important outcomes were determined for COS-CM-Hyperlipidemia. It included cardiovascular events, low-density lipoprotein cholesterol, risk of cardiovascular disease, total cholesterol, carotid intima-media thickness, high-density lipoprotein cholesterol, triglycerides, cerebrovascular events, adverse drug reactions and patient-reported symptoms.Conclusion: COS-CM-Hyperlipidemia may improve outcome reporting consistency in clinical trials. Further work is needed to explore the optimal methods for measuring these outcomes.Registration: The Core Outcome Measures in Effectiveness Trials Initiative (COMET): http://www.cometinitiative.org/studies/details/983. Registered on 25 April 2017.